Liquid metal material and preparation method thereof
By selecting a variety of elements and optimizing the ratio, liquid metal materials with high Vickers hardness and salt spray resistance were prepared, which solved the problem of poor compatibility between liquid metal materials and solid fillers, and significantly improved their mechanical strength and corrosion resistance.
Patent Information
- Application Number
- CN202411868059.2
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-18
- Publication Date
- 2025-03-07
- Estimated Expiration
- 2044-12-18
AI Technical Summary
The interface compatibility between liquid metal materials and solid fillers is poor, and interface defects or weak bonding areas are easily generated, affecting the mechanical strength of the composite material.
By selecting a variety of elements and working together, a liquid metal material has a high Vickers hardness at room temperature, and by optimizing the ratio of Sn, Zn and Al, the salt spray resistance of the amorphous alloy is improved.
It improves the Vickers hardness and elasticity limit of liquid metal materials, enhances its corrosion resistance and salt spray resistance, and improves mechanical strength and service life.
Smart Images

Figure SMS_1
Abstract
Description
Technical Field
[0001] The present invention belongs to the technical field of liquid metal materials, and in particular relates to a liquid metal material and a preparation method thereof. Background Art
[0002] Liquid metal is the common name for amorphous alloys. Amorphous alloy materials are considered to be the most promising new structural materials, and are widely used in machinery, medical, IT, electronics, military and other fields. Liquid metal technology, its liquid metal alloy materials have a unique amorphous molecular structure, which is completely different from the crystalline structure of traditional metals. This structure is closer to glass. The characteristics of liquid metal are low melting point, super strong shaping ability, high yield strength, high hardness, excellent strength-to-weight ratio, ultra-high elastic limit, corrosion resistance, high wear resistance and unique acoustic properties. And its biggest advantage lies in high plasticity, high strength and high hardness.
[0003] Liquid metal materials are able to transform from solid to liquid within a specific temperature range, which allows them to adapt to the temperature conditions downhole. Once the melted liquid metal material enters the cooler downhole environment, it quickly cools and re-solidifies into a solid, forming a strong sealing layer. This rapid solidification property helps shorten operation time and improve efficiency. The solidified liquid metal material usually has high mechanical strength and durability, can withstand the high pressure and high stress environment downhole, provide long-term and stable sealing effect, and reduce maintenance requirements.
[0004] Once the melted material enters the target area and begins to cool, it resolidifies into a solid, providing mechanical support and effective sealing. This is very important for preventing fluid leakage, protecting the wellbore structure, and maintaining the integrity of the oil or gas well. Liquid metal has potential application prospects as a plugging material due to its unique physical and mechanical properties. However, it also faces some technical challenges and problems: (1) Vickers hardness is a method of measuring the hardness of a material. It is determined by applying a fixed load on the surface of the material and measuring the diagonal length of the indentation. The higher the Vickers hardness value, the harder the material. High Vickers hardness means better resistance to wear. (2) Good corrosion resistance can prevent the plugging part from rusting or corroding, maintain its structural integrity and aesthetics, and reduce damage and replacement costs caused by corrosion. (3) High elastic limit means that when impacted by external force, materials with high elastic limit can absorb part of the energy, reduce the impact, and provide better protection.
[0005] In order to improve the mechanical properties of liquid metal materials, liquid metal is mixed with solid fillers such as ceramic particles, carbon nanotubes, and graphene to form a composite material. This can improve the hardness, wear resistance, and corrosion resistance of liquid metal while maintaining its excellent thermal conductivity. However, the interface compatibility between liquid metal and solid fillers is poor, and interface defects or weak bonding areas are easily generated. These interface problems will affect the mechanical strength of the composite material.
[0006] Therefore, there is an urgent need for a liquid metal material and a preparation method thereof. Summary of the invention
[0007] The purpose of the present invention is to provide a liquid metal material and a preparation method thereof. The liquid metal material is solid at 20-50°C, can melt at above 100°C, melt at high temperature and solidify at low temperature, and is used for underground plugging and casing annulus plugging.
[0008] In order to achieve the above object, the present invention provides the following technical solutions: A liquid metal material comprises the following raw materials in parts by mass: 10-18 parts of Cd, 10-20 parts of Pb, 25-30 parts of Bi, 4-17 parts of In, 5-15 parts of Al, 20-35 parts of Zn, 10-20 parts of Sn, and 8-20 parts of Nb.
[0009] Further, the total mass fraction of Pb and Cd is greater than the mass fraction of Bi.
[0010] When liquid metal materials are used for downhole plugging, it is very important to have a high Vickers hardness. The downhole environment is usually accompanied by extremely high pressure, especially in deep wells or high-pressure oil and gas fields. High-hardness materials can better resist this huge external pressure and prevent material deformation or damage, thereby ensuring the integrity and long-term stability of the plugging structure. During downhole operations, plugging materials may come into contact and friction with drilling tools, casing or other downhole equipment. High-hardness materials can reduce wear caused by mechanical movement, extend the service life of plugging materials, and reduce maintenance and replacement costs. At the same time, the fluid environment downhole is complex and diverse, and may contain acidic gases, brine and other corrosive substances. High-hardness materials tend to have better chemical stability and corrosion resistance, and can maintain their physical properties unchanged in harsh chemical environments. High-hardness materials can form a denser structure after curing, reduce porosity, and increase the density of the material. Such characteristics help to enhance the plugging effect and prevent fluid leakage, especially in situations where long-term sealing is required. In some cases, plugging materials not only need to play a sealing role, but also need to provide additional support for the well wall or casing. Materials with higher hardness are able to more effectively assume this support function and help maintain the structural integrity of the wellbore, especially when dealing with unstable formations or fractures. Materials with higher hardness generally have lower permeability, which means they are not easily penetrated by fluids such as oil, gas or water. This is critical to preventing fluid migration within the plugged area, especially when the plug is intended to isolate different production layers or prevent groundwater contamination. High-hardness plugging materials form a solid surface after curing, which makes subsequent downhole inspection and maintenance work easier. For example, the quality of the plug can be evaluated by non-destructive methods such as ultrasonic testing without worrying about the fragility of the material itself affecting the test results.
[0011] The present invention selects multiple elements and, through synergistic action, obtains a liquid metal material having a high Vickers hardness at room temperature. It is found in experiments that when the total mass fraction of Pb and Cd is greater than the mass fraction of Bi, the elastic limit of the liquid metal material can also be improved. Analysis shows that when the total mass fraction of Pb and Cd is greater than Bi, the proportion of low-melting-point elements in the alloy increases, which helps to form more amorphous regions during the cooling process. The amorphous structure does not have long-range ordered crystal defects, so it can better disperse stress and improve the elastic limit of the material. At the same time, the Vickers hardness at low temperatures is also improved under this condition.
[0012] Furthermore, the mass ratio of Sn:Zn:Al is (10-14):(23-27):(6-10).
[0013] There is often a large amount of salt water in the underground environment, especially for offshore oil and gas production, the chloride ions in seawater are extremely corrosive. Materials with high salt spray resistance can maintain their physical and chemical properties in such an environment, preventing material degradation, strength loss and sealing failure caused by corrosion. High salt spray resistance can significantly improve the durability and service life of plugging materials. Even in the case of long-term exposure to salt-containing fluids, the material will not be easily corroded or damaged, reducing the need for maintenance and replacement and reducing operating costs. In the present invention, when the mass fraction ratio of Sn: Zn: Al is (10-14): (23-27): (6-10), the salt spray resistance of the amorphous alloy can be improved. By optimizing the ratio of Sn, Zn and Al, the present invention can reduce the active sites on the alloy surface and reduce the probability of corrosion reaction. In particular, when the Al content is appropriate, it can work together with Sn and Zn to form a more stable surface structure and reduce the starting point of the corrosion reaction.
[0014] Furthermore, the following raw materials are included in parts by mass: 12-16 parts of Cd, 15-20 parts of Pb, 25-30 parts of Bi, 4-9 parts of In, 5-10 parts of Al, 22-27 parts of Zn, 10-14 parts of Sn, and 8-16 parts of Nb.
[0015] Furthermore, the following raw materials are included in parts by mass: 15 parts of Cd, 18 parts of Pb, 27 parts of Bi, 6 parts of In, 8 parts of Al, 25 parts of Zn, 13 parts of Sn, and 11 parts of Nb.
[0016] Furthermore, the purity of the raw material is ≥99.9%.
[0017] The present invention provides a method for preparing a liquid metal material, comprising the following steps: (1) Sn, Zn, and Al are placed in a crucible and smelted in a high-frequency heating furnace under the conditions of pre-evacuation and subsequent filling with argon gas to obtain a first alloy; (2) adding Pb, Cd and Nb to the first alloy, melting the alloy under the conditions of pre-evacuation and subsequent filling with argon gas, and fusing the alloy with the first alloy to obtain a second alloy; (3) adding the remaining raw materials to the second alloy, melting them under the conditions of pre-evacuation and subsequent filling with argon gas, and fusing them with the second alloy to obtain a third alloy; (4) The third alloy is stirred and naturally cooled to room temperature to obtain a liquid metal material.
[0018] Furthermore, the smelting temperature in step (1) is 950-960°C.
[0019] Furthermore, the smelting temperature in step (2) is 1000-1030°C.
[0020] Furthermore, the smelting temperature in step (3) is 1050-1080°C.
[0021] Furthermore, the stirring time in step (4) is 30-40 minutes.
[0022] Compared with the prior art, the advantages and beneficial effects of the present invention are: 1. The present invention selects a variety of elements and obtains a liquid metal material having a higher Vickers hardness through synergistic effect.
[0023] 2. When the total mass fraction of Pb and Cd is greater than the mass fraction of Bi, the elastic limit of the liquid metal material can also be improved.
[0024] 3. In the present invention, when the mass fraction ratio of Sn:Zn:Al is (10-14):(23-27):(6-10), the salt spray resistance of the amorphous alloy can be improved. DETAILED DESCRIPTION
[0025] The technical solutions in the embodiments of the present invention are described clearly and completely below. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of them. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0026] Example 1 The present embodiment provides a liquid metal material, comprising the following raw materials in parts by mass: 15 parts of Cd, 18 parts of Pb, 27 parts of Bi, 6 parts of In, 8 parts of Al, 25 parts of Zn, 13 parts of Sn, and 11 parts of Nb.
[0027] The purity of the raw material is ≥99.9%.
[0028] The method for preparing the liquid metal material comprises the following steps: (1) Sn, Zn and Al are placed in a crucible and melted in a high-frequency heating furnace under the conditions of pre-evacuation and subsequent filling with argon gas at a melting temperature of 950° C. to obtain a first alloy; (2) adding Pb, Cd and Nb to the first alloy, melting them under the conditions of pre-evacuation and subsequent filling with argon gas, and fusing them with the first alloy at a melting temperature of 1010° C. to obtain a second alloy; (3) adding the remaining raw materials to the second alloy, melting them under the conditions of pre-vacuuming and then filling them with argon at a melting temperature of 1060° C., and fusing them with the second alloy to obtain a third alloy; (4) Stirring the third alloy for 40 minutes and naturally cooling it to room temperature to obtain a liquid metal material.
[0029] Example 2 The present embodiment provides a liquid metal material, comprising the following raw materials in parts by mass: 12 parts of Cd, 20 parts of Pb, 25 parts of Bi, 4 parts of In, 10 parts of Al, 22 parts of Zn, 14 parts of Sn, and 8 parts of Nb.
[0030] The purity of the raw material is ≥99.9%.
[0031] The method for preparing the liquid metal material comprises the following steps: (1) Sn, Zn and Al are placed in a crucible and melted in a high-frequency heating furnace under the conditions of pre-evacuation and subsequent filling with argon gas at a melting temperature of 950° C. to obtain a first alloy; (2) adding Pb, Cd and Nb to the first alloy, melting them under the conditions of pre-evacuation and subsequent filling with argon gas, and fusing them with the first alloy at a melting temperature of 1000° C. to obtain a second alloy; (3) adding the remaining raw materials to the second alloy, melting them under the conditions of pre-evacuation and subsequent filling with argon at a melting temperature of 1080° C., and fusing them with the second alloy to obtain a third alloy; (4) Stirring the third alloy for 40 minutes and naturally cooling it to room temperature to obtain a liquid metal material.
[0032] Comparative Example 1 The difference between this comparative example and Example 1 is: a liquid metal material, comprising the following raw materials in parts by mass: 20 parts of Cd, 23 parts of Pb, 22 parts of Bi, 1 part of In, 3 parts of Al, 25 parts of Zn, 23 parts of Sn, and 6 parts of Nb.
[0033] Comparative Example 2 The difference between this comparative example and Example 1 is: a liquid metal material, comprising the following raw materials in parts by mass: 5 parts of Cd, 23 parts of Pb, 20 parts of Bi, 20 parts of In, 15 parts of Al, 11 parts of Zn, 23 parts of Sn, and 6 parts of Nb.
[0034] Comparative Example 3 The difference between this comparative example and Example 1 is that the total mass fraction of Pb and Cd is less than the mass fraction of Bi.
[0035] A liquid metal material comprises the following raw materials in parts by mass: 20 parts of Cd, 8 parts of Pb, 32 parts of Bi, 6 parts of In, 8 parts of Al, 25 parts of Zn, 13 parts of Sn, and 11 parts of Nb.
[0036] Comparative Example 4 The difference between this comparative example and Example 1 is that the mass fraction ratio of Sn:Zn:Al is not within the range of (10-14):(23-27):(6-10).
[0037] A liquid metal material comprises the following raw materials in parts by mass: 15 parts of Cd, 18 parts of Pb, 27 parts of Bi, 6 parts of In, 3 parts of Al, 35 parts of Zn, 8 parts of Sn, and 11 parts of Nb.
[0038] Comparative Example 5 The difference between this comparative example and Example 1 is: The preparation method of the liquid metal material comprises the following steps: placing all raw materials into a crucible, and using a high-frequency heating furnace to melt under the conditions of pre-vacuuming and then filling with argon, the melting temperature is 1000°C, the stirring time is 40 minutes, and the liquid metal material is naturally cooled to room temperature.
[0039] Comparative Example 6 The difference between this comparative example and Example 1 is: The method for preparing the liquid metal material comprises the following steps: (1) Sn, Zn and Al are placed in a crucible and melted in a high-frequency heating furnace under the conditions of pre-evacuation and subsequent filling with argon gas at a melting temperature of 960° C. to obtain a first alloy; (2) adding the remaining raw materials into the first alloy, melting the first alloy under the conditions of pre-evacuation and subsequent filling with argon gas at a melting temperature of 1000° C., and fusing the first alloy with the second alloy to obtain a second alloy; (3) Stirring the second alloy for 40 minutes and naturally cooling it to room temperature to obtain a liquid metal material.
[0040] Performance Testing The liquid metal materials prepared in Examples 1-2 and Comparative Examples 1-6 were subjected to performance tests, including Vickers hardness, corrosion resistance (salt spray test), and elastic limit, wherein the Vickers hardness was measured in accordance with the standard of ASTM E92-82; the salt spray test was measured in accordance with the standard of ASTM B117-2011. The elastic limit was measured in accordance with the standard of GB / T 22315-2008.
[0041] Table 1 Performance test results
[0042] It can be seen from the above performance test results that the comprehensive performance of the liquid metal materials of Examples 1-2 is excellent, especially the comprehensive performance of Example 1 is the most outstanding, which is mainly due to the synergistic effect between the elements and the synergistic effect of the preparation method.
[0043] The comparative examples, however, are significantly inferior to the embodiments in the corresponding performance tests because they do not adopt the necessary technical solutions. In comparative examples 1 and 2, the raw material ratios are changed, and it can be seen that the comprehensive effect of the liquid alloy decreases. In comparative example 3, when the total mass fraction of Pb and Cd is less than the mass fraction of Bi, the elastic limit of the liquid metal material decreases, and the Vickers hardness at low temperature decreases. In downhole plugging applications, the difference in the Vickers hardness of liquid metal materials at 10°C and 25°C has important engineering significance. The temperature of the downhole environment varies greatly, especially in deep wells or different geological formations, where the temperature may vary from low temperature (such as 10°C) to high temperature (such as above 100°C). Understanding the hardness changes of materials at different temperatures helps to select the most suitable materials for specific downhole conditions. For example, if the downhole temperature is low (such as 10°C), it is necessary to ensure that the material still maintains sufficient hardness and strength at low temperatures to provide effective plugging. The hardness change of the material is closely related to its thermal expansion coefficient. When the temperature changes, the volume of the material will also change, which may affect the integrity and sealing effect of the plugging structure. By studying the hardness changes at 10℃ and 25℃, the thermal expansion behavior of materials at different temperatures can be better predicted, thereby optimizing the design. In downhole plugging operations, materials usually need to melt into liquid at higher temperatures to facilitate injection into the target area. However, during the construction process, the downhole temperature may fluctuate. Understanding the hardness changes of materials at 10℃ and 25℃ can help engineers determine the optimal construction temperature range to ensure that the material has appropriate fluidity when injected, and can quickly solidify and form a solid plugging layer after cooling. The hardness change of the material will also affect its curing time. At lower temperatures (such as 10℃), the material may take longer to fully cure, while at higher temperatures (such as 25℃), the curing speed may be faster. Mastering this feature helps optimize the construction process and ensure that the plugging material reaches the required hardness and strength in the appropriate time. The downhole environment is usually accompanied by extremely high pressure, especially in deep wells or high-pressure oil and gas fields. The hardness of the material directly determines its compressive strength and deformation resistance. The hardness values measured at 10°C and 25°C can help evaluate the compressive performance of the material at different temperatures and ensure that it will not deform or fail due to pressure during long-term use. One of the main functions of plugging materials is to prevent fluid leakage. The change in the hardness of the material directly affects its sealing effect. Under low temperature conditions, the increase in the hardness of the material may make it more dense and reduce porosity, thereby improving the sealing performance. Therefore, understanding the change in hardness at 10°C and 25°C can help ensure that the plugging material can provide a reliable seal at different temperatures to prevent the leakage of oil, gas or water. The high-hardness plugging material forms a solid surface after curing, which makes subsequent downhole inspection and maintenance work easier. For example, the quality of the plugging can be evaluated by non-destructive methods such as ultrasonic testing, without worrying about the fragility of the material itself affecting the test results.Understanding the hardness changes at 10°C and 25°C helps to select materials suitable for subsequent operations and ensure smooth maintenance work. When the mass fraction ratio of Sn:Zn:Al in Comparative Example 4 is not in the range of (10-14):(23-27):(6-10), the salt spray resistance of the liquid metal material decreases. The preparation methods in Comparative Examples 5 and 6 are different, and the comprehensive performance of the liquid metal decreases. Mixing all the components at one time may cause some elements to fail to fully dissolve or evenly distribute, thereby forming defects in the alloy. Adding them in batches can reduce the generation of these defects and improve the overall quality of the alloy. Adding them in batches allows the melting temperature to be gradually adjusted to ensure that the reaction conditions at each stage are optimized. The above experimental results further demonstrate the importance of the technical scheme defined in the present invention for its technical effects.
[0044] The above is a preferred embodiment of the present invention. It should be pointed out that for ordinary technicians in this technical field, several improvements and modifications can be made without departing from the principles of the present invention. These improvements and modifications should also be regarded as the scope of protection of the present invention.
Claims
1. A liquid metal material, characterized in that: The invention comprises the following raw materials in parts by weight: 10-18 parts of Cd, 10-20 parts of Pb, 25-30 parts of Bi, 4-17 parts of In, 5-15 parts of Al, 20-35 parts of Zn, 10-20 parts of Sn and 8-20 parts of Nb.
2. The liquid metal material according to claim 1, characterized in that: The total mass fraction of Pb and Cd is greater than the mass fraction of Bi.
3. The liquid metal material according to claim 2 is characterized in that the mass fraction ratio of Sn:Zn:Al is (10-14):(23-27):(6-10).
4. The liquid metal material according to claim 3, characterized in that: The invention comprises the following raw materials in parts by mass: 12-16 parts of Cd, 15-20 parts of Pb, 25-30 parts of Bi, 4-9 parts of In, 5-10 parts of Al, 22-27 parts of Zn, 10-14 parts of Sn and 8-16 parts of Nb.
5. The liquid metal material according to claim 4, characterized in that: The invention comprises the following raw materials in parts by mass: 15 parts of Cd, 18 parts of Pb, 27 parts of Bi, 6 parts of In, 8 parts of Al, 25 parts of Zn, 13 parts of Sn and 11 parts of Nb.
6. The liquid metal material according to claim 1, characterized in that: The purity of the raw material is ≥99.9%.
7. A method for preparing the liquid metal material according to any one of claims 1 to 6, characterized in that: The following steps are involved: (1) Sn, Zn, and Al are placed in a crucible and smelted in a high-frequency heating furnace under the conditions of pre-evacuation and subsequent filling with argon gas to obtain a first alloy; (2) adding Pb, Cd and Nb to the first alloy, melting the alloy under the conditions of pre-evacuation and subsequent filling with argon gas, and fusing the alloy with the first alloy to obtain a second alloy; (3) adding the remaining raw materials to the second alloy, melting them under the conditions of pre-evacuation and subsequent filling with argon gas, and fusing them with the second alloy to obtain a third alloy; (4) The third alloy is stirred and naturally cooled to room temperature to obtain a liquid metal material.
8. The method for preparing liquid metal material according to claim 7, characterized in that: The smelting temperature in step (1) is 950-960°C.
9. The method for preparing liquid metal material according to claim 7, characterized in that: The smelting temperature in step (2) is 1000-1030°C.
10. The method for preparing liquid metal material according to claim 7, characterized in that: The smelting temperature in step (3) is 1050-1080°C.
Citation Information
Patent Citations
Bismuth-based liquid metal with melting point lower than 50 DEG C and preparation method thereof
CN113969370A
Metal-alloy biphasic systems, and powders and methods for making metal-alloy biphasic systems
US12037669B1
Architected liquid metal networks and processes of making and using same
US20200146142A1
Method for manufacturing metal phase transition-based flexible electronic material and application of same
WO2023197491A1